PERENCANAAN SISTEM MANAJEMEN KEAMANAN INFORMASI BERDASARKAN STANDAR ISO 27001:2013 PADA KOMINFO KABUPATEN MALANG - Setyaningrum, Anis; Kurniawan, Yudhi; Setiawan, Rudy (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2023)
The Department of Communication and Information (DISKOMINFO) of Malang Regency is a Regional Apparatus (PD) that utilizes Information and Communications Technology (ICT). Regarding the importance of implementing ICT Governance for the Information Security Management System, as stipulated in Presidential Regulation No. 95 of 2018 on Electronic-Based Government Systems (SPBE) and the Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 4 of 2016, all government agencies are required to implement security management for all the information they handle. The method used in this study to address the discussed issues involves developing policies and standard operating procedures (SOPs) and assessing information security risks in organizational assets, referring to the ISO/IEC 27001:2013 standard as a guideline for information security management. The reason for using these standards is that the Indonesian government, through the National Standardization Body (BSN), has designated SNI ISO/IEC 27001:2013 as the national standard (SNI) for managing information security for organizations of all types and sizes. The result of this research is the creation of information security policy documents and SOP documents to enhance security controls within information security management systems based on ISO/IEC 27001:2013.